Heliotropium; a genus rich in pyrrolizidine alkaloids: A systematic review following its phytochemistry and pharmacology - Marwa A.A. Fayed (Phytomedicine Plus, 2021)
Introduction: A huge number of plants have remedial and therapeutic prospects throughout the world and are used in the treatment of diverse diseases. Heliotropium is a large genus of family Boraginaceae which widely distributed in tropical and temperate regions of hemispheres. The purpose of this review is to recapitulate the phytochemistry and pharmacological activities of the Heliotropium species to unveil future research prospects. Methods: Published data in this review were all gathered from the online bibliographical databases: PubMed, Elsevier, Scopus, Google Scholar and Web of Science. Results: The plants of the Heliotropium genus in the history of traditional drugs provide remedies for gout, inflammation, skin disorders, menstrual dysfunction, rheumatism, and noxious bites. The active biochemical constituents extracted from the Heliotropium species comprise pyrrolizidine alkaloids, flavonoids, and terpenoids. Significant biological activities viz. antimicrobial, antiviral, antitumor, anti-inflammatory, cytotoxicity, phytotoxicity, and wound healing were revealed by an enormous number of extracts and biochemically active constituents of various species of the Heliotropium genus. Conclusion: Phytomedicines are now an important and beneficial zone of the recommended treatment and have high potentials in many countries. Although this clear evidence that plants of the Heliotropium genus have several medicinal importance in the treatment of diverse diseases. The medicinal use of these plants as phyto-pharmaceuticals would depend on the production of the required systematic procedures necessary to standardize the various bioactive secondary metabolites in such herbal formulations. Therefore, we conclude that in the coming period, plants of the Heliotropium genus would become an acceptable source of indigenous medicines.